Un documento di pattuizione tra il voevoda bosniaco voevoda Sandalj Hranić Kosača e la Repubblica di Venezia: genesi e modelli - Lomagistro, Barbara (Scrineum, 2021)
The paper analyzes a charter issued by the Bosnian voevoda Sandalj Hranić Kosača sealing the agreement established with Venice in consequence of the entry of Kotor in the Venetian Commonwealth (1423). The analysis focuses on document's formal aspects in order to identify the underlying documentary model. For this purpose, all the linked records produced by Venice on this occasion are taken into account. Moreover, an attempt to relate the documentation of Kotor affair to the Venetian practice in making documents about treaties is provided. Such an analysis leads to the conclusion that the Venetian documentary patterns developped for sealing international agreements were adopted in Slavic version of the documentation too.